Olefin oligomerisation over nanocrystalline MFI-based micro/mesoporous zeotypes synthesised via bottom-up approaches. (August 2019) - Silva, Andreia F.; Fernandes, Auguste; Antunes, Margarida M.; Ribeiro, Maria F.; Silva, Carlos M.; Valente, Anabela A.
Abstract: The oligomerisation of 1-butene was studied under high-pressure continuous-flow conditions (200–250 °C, 30–40 bar), in the presence of micro/mesoporous zeotypes based on the MFI topology, which were prepared via different non-destructive bottom-up strategies: crystallization of silanized protozeolitic units; co-templating with a dual function (polymeric) template; and using a sole structure directing agent (non-surfactant and non-polymeric) to generate mesoporosity. The synthesis method influenced the material properties and consequently the catalytic performance. In targeting hydrocarbons with boiling point ranges characteristics of diesel, the zeotypes benefited from regular morphology, reduced crystallite size, mesoporosity and enhanced molar ratio of Lewis (L) to Brønsted (B) acid sites (L/B). In general, the zeotypes outperformed commercial zeolite ZSM-5. The best-performing zeotype was prepared according to the Serrano strategy based on the crystallization of silanized zeolitic seeds, and led to 97% conversion and an average space-time yield of liquid products of 1077 mg gcat −1 h −1, at 250 °C, 40 bar. The zeotypes seemed more stable than the commercial zeolite, based on molecular level characterization studies of the used/regenerated catalysts, with some differences in catalytic activity. Graphical abstract: Image 1 Highlights: Olefins to diesel type products via oligomerisation over MFI-based catalysts. Non-destructive synthetic bottom-up approaches to micro/mesoporous nano-zeotypes. Regular morphology, nanocrystallites, mesoporosity, L/B favour catalytic performance. Zeotypes outperformed commercial ZSM-5 which possessed greater amount of acid sites.